Can biomechanical testing after anterior cruciate ligament reconstruction identify athletes at risk for subsequent ACL Injury to the contralateral uninjured limb? - King, E.; Richter, C.; Daniels, K. A. J.; Franklyn-Miller, A.; Falvey, E.; Myer, G. D.; Jackson, M.; Moran, R.; Strike, S. (The American Journal of Sports Medicine, 2021)
Background: Athletes are twice as likely to rupture the anterior cruciate ligament (ACL) on their healthy contralateral knee than the reconstructed graft after ACL reconstruction (ACLR). Although physical testing is commonly used after ACLR to assess injury risk to the operated knee, strength, jump, and change-of-direction performance and biomechanical measures have not been examined in those who go on to experience a contralateral ACL injury, to identify factors that may be associated with injury risk.